Identifying Hemostatic Thresholds in Cancer Patients Undergoing Coronary Angiography Based on Platelet Count and Thromboelastography - Agha, Ali M.; Gill, Clarence; Balanescu, Dinu Valentin; Donisan, Teodora; Palaskas, Nicolas; Lopez-Mattei, Juan; Hassan, Saamir; Kim, Peter Y.; Charitakis, Konstantinos; Cilingiroglu, Mehmet; Oo, Thein Hlaing; Kroll, Michael; et al. (Frontiers in Cardiovascular Medicine, 2020)
Objectives: To evaluate the role of platelet count and thromboelastogram (TEG) in the treatment of thrombocytopenic cancer patients with suspected coronary artery disease (CAD). Background: Cancer patients with CAD and thrombocytopenia are often treated non-invasively (i.e., without coronary angiography when clinically indicated) due to perceived high risk of bleeding. We sought to evaluate coagulability based on TEG and determine if platelet count and TEG could predict bleeding risk/mortality among cancer patients undergoing coronary angiography (CA). Methods: Baseline demographics, platelet count, and TEG parameters were recorded among cancer patients that underwent CA and had a concomitant TEG. Logistic regression and univariate proportional hazards regression analysis were performed to determine the impact of platelet count and coagulability on 24-month overall survival (OS). Results: All patients with platelet count <20,000/mm3 and nearly all patients with platelet count 20,000–49,000/mm3 were hypocoagulable based on TEG results. In contrast, nearly all patients with platelet counts of 50,000–99,999/mm3 had normal TEG results and OS similar to those with platelet counts of ≥100,000/mm3. Coagulability based on TEG was not associated with OS. However, a platelet count of <50,000/mm3 was associated with worse 24-month OS (hazard ratio = 2.76; p = 0.0072) when compared with a platelet count of ≥100,000/mm3. No major bleeding complications were observed in all groups. Conclusion: The majority of cancer patients with platelet counts of <50,000/mm3 were hypocoagulable based on TEG and had worse OS at 24 months. The relatively normal TEGs in the >50,000/mm3 groups, as well as the improved survival, suggest that with appropriate clinical indication and risk/benefit assessment, a cut-off of 50,000/mm3 platelets can be considered for CA in cancer patients.